Khidmah System as a Model for Human Resources Development and Character Education in Islamic Boarding Schools - Aji Wahyudin; Rohmad Rohmad; Fadhil Akbar (JURNAL ISLAM NUSANTARA, 2025)
This study examines the Khidmah System as a model for human resource development and character education at the Salaf Darussalam Islamic Boarding School, Sumbersari, Kediri. The focus of the research includes the implementation of solemnity, its contribution to the competence and character of students, and the challenges of its application in the modern era. The method used is qualitative with the type of case study research through observation, in-depth interviews, and documentation analysis. The results of the study show that khummah runs as an experiential learning mechanism that fosters discipline, responsibility, solidarity, basic leadership, and social skills of students. However, there are challenges in the form of the absence of written SOPs, inequality in the workload, and disruption of the use of gadgets. The research concludes that the Khidmah System has the potential to be a model of character education that can be replicated in other Islamic boarding schools, provided that it is strengthened through formal regulations, intensive coaching, and adaptation to technological developments.